Trans-Endodontic Zirconium Oxide Implants: A Clinical Alternative - Aguilera-Galaviz DDS, MSc, PhD, Luis; Larios-Cervantes DDS, Alexis; Flores-Reyes DDS, MSc, PhD, Hector; Baltazar DDS, MSc, PhD, Victor; Gaitan-Fonseca DDS, MSc, PhD, Cesar (Odovtos - International Journal of Dental Sciences, 2019)
Dental trauma, mainly from the anterior area of the mouth in the incisor teeth at the level of the radicular third, has the extraction of the dental organ as an elective treatment, depending on the severity of the lesion and the site where it presented. This paper reports two cases: one in a young 13-year-old male patient with dental trauma in central incisors, and another in an 18-year-old female patient with radicular reabsorption in central incisors. Both were treated using trans-endodontic implants on teeth 2.1 and 1.1-2.2 each case, respectively. The treatment approach proposed for each case provided good functional and esthetic outcomes. Clinical and radiographic results after 1 year were successful.